Exploring shared surgical decision‐making from the patient's perspective: is the personality of the surgeon important?. (30th July 2020) - Bisset, C. N.; Dames, N.; Oliphant, R.; Alasadi, A.; Anderson, D.; Parson, S.; Cleland, J.; Moug, S. J.
Abstract: Aim: The aim was to determine the importance of a colorectal surgeon's personality to patients and its influence on their decision‐making. Methods: We present a two‐part mixed methods study using the Guidance for Reporting Involvement of Patients and the Public (GRIPP‐2) long form. Part 1 was an online survey (25 questions) and Part 2 a face‐to‐face patient and public involvement exercise. Part 1 included patient demographics, details of surgery, overall patient satisfaction (net promoter score) and patient views on surgeon personality (Gosling 10 Item Personality Index). The thematic analysis of free‐text responses generated four themes that were taken forward to Part 2. These themes were used to structure focus group discussions on surgeon–patient interactions. Results: Part 1 yielded 296 responses: 72% women, 75.3% UK‐based and 55.1% aged 40–59 years. Inflammatory bowel disease (45.3%) and cancer (40.2%) were the main indications. 84.1% of respondents reported satisfaction with their surgical experience (net promoter score). Four key themes were generated from Part 1 and validated in Part 2: (i) surgeon personality stereotypes (media differed from patients' perspective); (ii) favourable and unfavourable surgical personality traits (openness, conscientiousness, emotional stability preferred over risk‐taking and narcissism); (iii) patient–surgeon interaction (mutual respect and rapport valued); (iv) impact of surgeon personality on decision‐making (majority unaware of second opinion option; management of postoperative complications). Conclusion: Patients believe surgeon personality influences shared decision‐making. Low levels of emotional stability and conscientiousness are perceived by patients to increase the likelihood of postoperative adverse events. Further work is required to explore the potential influence of surgeon personality on shared decision‐making and postoperative outcomes.